Retraction Note: A Complete Formula of Ocean Surface Absolute Geostrophic Current - Peter C. Chu (Nature Portfolio, 2021)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-021-86517-3 .